THE EFFECT OF TRAINING ON PERFORMANCE MEDIATED BY WORK COMPETENCE AMONG EMPLOYEES OF THE CIVIL SERVICE POLICE UNIT (SATPOL PP) OF DENPASAR CITY - Anak Agung Sagung Indira Maharani; I Gusti Ayu Dewi Adnyani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the effect of training on employee performance with work competence as a mediating variable at the Civil Service Police Unit (Satpol PP) of Denpasar City. This study was conducted to understand the extent to which training can develop work competence and how such competence contributes to the improvement of employee performance. The study employed a survey approach involving 43 employees as the sample. The research instrument was a questionnaire measured using a Likert scale. The analytical technique used was Structural Equation Modeling (SEM) based on variance or component-based SEM with the SmartPLS application. The testing was carried out through measurement model analysis (outer model) and structural model analysis (inner model), including validity testing, reliability testing, R-square values, and hypothesis testing using bootstrapping. The results show that training does not have a significant effect on employee performance. Training has been proven to have a positive and significant effect on work competence. Work competence was also found to have a positive and significant effect on employee performance. In addition, training has an effect on employee performance indirectly through work competence as a mediating variable. The R-square results indicate that work competence and performance have a moderate level of ability in explaining the model. This study provides theoretical contributions to Human Capital Theory by confirming that training can improve performance when the training has first succeeded in improving employees’ work competence